The last king of Angkor Wat - Base, Graeme (Abrams Books for Young Readers, 2014)
Among the ruins of Angkor Wat, Tiger, Gibbon, Water Buffalo, and Gecko accept Elephant's challenge to race to a certain temple to settle their argument over who would have made the greatest king, and at the end Elephant explains how the competition showed each one's strengths and weaknesses. Includes search-and-find illustrations and a brief history of the "City of Temples."